Method of Evaluating Multiple Scenarios in a Single Simulation Run for Automated Vehicle Assessment - Kim, Inyoung; Kang, Donghyo; Jeong, Harim; Lee, Soomok; Yun, Ilsoo (Sensors, 2023)
With advances in the technology applied to automated driving systems (ADSs), active efforts have been made to evaluate the safety of ADS in various complex situations using simulations. In accordance with these efforts, numerous institutions have developed single-scenario pools that reflect a variety of road and traffic characteristics and ADS performances. However, a single scenario has limitations in comprehensively evaluating the performance of complex ADS. Therefore, this study proposed a methodology that combines and transforms single scenarios into multiple scenarios. This aided in continuously evaluating the ADS performance over entire road segments and implemented this methodology in the simulations.
Keywords: Automated driving systems; Automated vehicles; Driving safety; Driving system performance; Multi scenarios; Performance; Road segments; Scenario acceleration; Simulation; Traffic characteristics; automated vehicle; driving safety; multi-scenarios; scenario acceleration; simulation